2005
DOI: 10.1079/wps200445
|View full text |Cite
|
Sign up to set email alerts
|

The role of the commensal gut microbial community in broiler chickens

Abstract: To understand the relationship between the gastrointestinal inhabiting microbial community and broiler health, a literature review is presented. The available information on the development of gut microbial community, the relationship between commensal microflora and digestive function, the role of gut microorganisms on competitive exclusion of chickens against pathogens, and modulation of the gut microbial community by addition of prebiotics to the diet is summarized. Gut dominant microbial communities become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
167
1
32

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(203 citation statements)
references
References 71 publications
3
167
1
32
Order By: Relevance
“…In fact, the groups 0.5 LB and 1.0LB negatively affected the left cecum diameter, probably due to a villi underdevelopment, and both findings can be related. The gut microflora enhancement and low cecal development can justify, at least partially (Lu et al, 2003;Lan et al, 2005), the poorly indexes efficiency observed in the present study.…”
Section: Discussionmentioning
confidence: 71%
“…In fact, the groups 0.5 LB and 1.0LB negatively affected the left cecum diameter, probably due to a villi underdevelopment, and both findings can be related. The gut microflora enhancement and low cecal development can justify, at least partially (Lu et al, 2003;Lan et al, 2005), the poorly indexes efficiency observed in the present study.…”
Section: Discussionmentioning
confidence: 71%
“…Também, mostrou-se o efeito nutricional dos probióticos mediante o estímulo à produção de enzimas como a lactase e pela manutenção saudável das vilosidades intestinais, as quais melhoram a digestibilidade de alimentos e a absorção de nutrientes (LAN et al, 2005).…”
Section: Introductionunclassified
“…The dietary composition (Teo and Tan, 2007), microflora (Lan et al, 2005), and the interaction between the diet and microflora can affect the intestinal development, mucosal architecture and the mucus composition of the gastrointestinal tract (Apajalahti et al, 2004;Teirlynck et al, 2009). Losada and Olleros (2002) found that the intestinal flora naturally contain both healthy and unhealthy bacteria.…”
Section: Introductionmentioning
confidence: 99%